Identifying age penalty in women's wages: New method and evidence from Germany 1984-2014 - Joanna Tyrowicz; Lucas Van der Velde; Irene van Staveren (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2018)
Given theoretical premises, gender wage gap adjusted for individual characteristics is likely to vary over age. We extend DiNardo, Fortin and Lemieux (1996) semi-parametric technique to disentangle year, cohort and age effects in adjusted gender wage gaps. We rely on a long panel of data from the German Socio-Economic Panel covering the 1984-2015 period. Our results indicate that the gender wage gap increases over the lifetime, for some birth cohorts also in the post-reproductive age.
Keywords: J31; J71; 330; gender wage gap; age; cohort; decomposition; non-parametric estimates; Germany